Comparative Analysis of Individual Carotenoid Profiles in Yellow- and White-Fleshed Potatoes (Solanum tuberosum L.) During Tuber Development - Suo, Haicui; Liu, Jitao; Wang, Li; Li, Chengchen; Shan, Jianwei; An, Kang; Yang, Kun; Li, Xiaobo (Foods, 2024)
Individual carotenoids provide significant health benefits to humans, and potatoes are recognized as some of the most stable crops, distinguished by their substantial carotenoid content. To elucidate the accumulation patterns of individual carotenoids in potatoes, we quantified the carotenoid content in yellow- and white-fleshed genotypes across five developmental stages using LC-MS/MS. A total of 22 carotenoids were identified in yellow potatoes, whereas 18 were detected in white potatoes. The yellow-fleshed genotype was characterized by high levels of individual carotenoids and xanthophyll esters, with violaxanthin as the dominant component. The white-fleshed genotype exhibited low concentrations of individual carotenoids and xanthophyll esters, with lutein as the predominant compound. Notably, lutein, violaxanthin, zeaxanthin, antheraxanthin, neoxanthin, violaxanthin myristate, and lutein myristate were consistently detected during the developmental period in both genotypes. Violaxanthin myristate was identified as the dominant xanthophyll ester in both genotypes, showing an increasing trend throughout the tuber development stages. In contrast, xanthophyll esters maintained stable low levels in white-fleshed potatoes while exhibiting increasing types and contents in yellow-fleshed potatoes as the tubers continued to grow. Additionally, violaxanthin exhibited a significant correlation with b*, H°, and C*, suggesting that it may play an important role in forming yellow flesh.